2018
DOI: 10.1287/ijoc.2017.0759
|View full text |Cite
|
Sign up to set email alerts
|

Space Reduction for a Class of Multidimensional Markov Chains: A Summary and Some Applications

Abstract: In this paper, we present examples of a class of Markov chains that occur frequently, but whose associated matrices are a challenge to construct efficiently. These are Markov chains that arise as a result of several identical Markov chains running in parallel. Specifically for the cases considered, both the infinitesimal generator matrix for the continuous case, and more so the transition probability matrix for the discrete equivalent, are complex to construct effectively and efficiently. We summarize the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In this work, the construction of a multi-dimensional Markov chain (MDMC) describing the dynamics of the system, including the proper choice of the components defining the service and retrial processes, is required for the analysis of a multi-server queuing system with PH distributed service and retrial times. There are two different ways, referred to as the TPFS (track-phase-for-server) and CSFP (count-server-for-phase) ( [16]), to keep track of the phases for service and retrial processes. In this work, CSFP approach is employed for the sake of performing computation in an efficient way since it provides comparatively much smaller state space than TSFP.…”
Section: State Of the Artmentioning
confidence: 99%
“…In this work, the construction of a multi-dimensional Markov chain (MDMC) describing the dynamics of the system, including the proper choice of the components defining the service and retrial processes, is required for the analysis of a multi-server queuing system with PH distributed service and retrial times. There are two different ways, referred to as the TPFS (track-phase-for-server) and CSFP (count-server-for-phase) ( [16]), to keep track of the phases for service and retrial processes. In this work, CSFP approach is employed for the sake of performing computation in an efficient way since it provides comparatively much smaller state space than TSFP.…”
Section: State Of the Artmentioning
confidence: 99%
“…Although it has been simply presented in ref. [29] that the order statistics of multidimensional Markov chains is a Markov chain, there are still no specific methods of representing the state space and constructing the transition probability matrix of this Markov chain because of the difficulty of such a problem. The existing literature on Markov chains in the field of wireless communication is briefly given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Yevkin 35 proposed an approximate Markov chain method for dynamic FTA to reduce the number of states in the model, but it is fault oriented; when the number of system fault states is large, the analysis is very complex. He and Alfa 36 demonstrated that the space complexity of Markov chains can be significantly reduced by using the count-server-for-phase (CSFP) approach, but the creation of the Markov chains is quite involved.…”
Section: Introductionmentioning
confidence: 99%